Are quinolone eardrops safe? New data on the association with persistent tympanic membrane perforation - Andrea Lovatoa (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Recently Alrwisan et colleagues [1] compares the rates of tympanic membrane (TM) perforation after use of the two available classes of eardrops, quinolones and neomycin, following ear tube surgery. Considering a total of 96,595 children, they found an increased risk of TM perforation requiring tympanoplasty in children which used quinolone eardrops. The adjusted hazard ratios were 1.49 (95% confidence interval [CI], 1.05-2.09) for ofloxacin, 1.94 (95% CI, 1.32-2.85) for ciprofloxacin plus hydrocortisone, and 2.00 (95% CI, 1.18-3.41) for ciprofloxacin. A recent cell culture study showed that treatment of mouse TM fibroblasts with ciprofloxacin, at concentrations similar to those achieved with eardrops in humans, led to marked cytotoxicity and depression in collagen synthesis [2]. These findings, together with the well-known detrimental effect of systemic quinolones on human collagenous tissue [3], raise suspicions about quinolone eardrops, as they could contribute to the development of persistent TM perforations. Clinicians are stuck in a difficult situation, as alternative eardrops with aminoglycosides have been known to cause hearing loss in the presence of TM perforation [4]